Androgen regulated protein and pyruvate dehydrogenase kinase 4 in severe erectile dysfunction: A gene expression analysis, and computational study of protein structure - Kazemi, Elham; Zargooshi, Javaad; Dehpahni, Mozhgan Fatahi; Mohammadi Motlagh, Hamid-Reza; Kaboudi, Marzieh; Kahrizi, Danial; Khazaie, Habibolah; Mahaki, Behzad; Mohammadian, Youkhabeh; Yazdani, Leila (Cellular and Molecular Biology, 2021)
Erectile dysfunction (ED) is one of the most common sexual disorders in men. During the past 30 years, there has been no new drug development for ED. Thus, exploring the genetic basis of ED deserves further study, in hope of developing new pharmacological treatments for ED. In this study, Real-Time PCR analysis was used to assess the expression of androgen regulatory protein (Andpro) and pyruvate dehydrogenase kinase 4 (Pdk4) genes in ED. For this purpose, the experiment was performed on 20 men with severe ED and 20 potent men. IIEF-15 was used to determine the ED severity. The study was conducted in the Department of Sexual Medicine of the Kermanshah University of Medical Sciences, Kermanshah, Iran. The EDTA-Na vacuum blood tube was taken from ED patients and controls. Informed consent was obtained from all participants. After blood sampling, RNA was extracted from whole blood. Then cDNA was synthesized. The gene expression was analyzed through the qPCR method. The ß-actin was used as a reference gene. To further study these two proteins, their three-dimensional structures were predicted through I-TASSER. Compared with controls, in ED patients, the expression of the Andpro gene decreased, while the expression of the Pdk4 gene increased (p<0.01). Predicting the structure of the protein showed that Pyruvate Dehydrogenase Kinase 4 had a double subunit and androgen-regulated protein had a single subunit.